Optimal design of a small size trigeneration plant in civil users: A MINLP (Mixed Integer Non Linear Programming Model) - Arcuri, P.; Beraldi, P.; Florio, G.; Fragiacomo, P. (Energy (Oxford), 2015)
An optimization procedure for the optimal design of a trigenerative system to satisfy the energy needs of civil users is proposed. For the formulation of the mathematical model, it was necessary to refer to the class of MINLP (Mixed Integer Non Linear Programming Models), whose complexity is related to the presence of binary decision variables and to the non linear nature of the constraints. These constraints are required to model the variation of the nominal efficiency and of the plant unitary cost in relation to the size of the cogeneration plant, and to model the decrease of the nominal efficiency of the cogeneration plant in relation to load variation. Different plant alternatives (Simple Cycle Gas Turbine, Gas Micro-Turbine, Gas Internal Combustion Engine, Fuel Cells) in the optimization procedure are taken into account with the aim of determining the optimal typology, size and operative strategy of the trigeneration system. •Optimization procedure for optimal design of a trigenerative system.•A Mixed Integer Non Linear Programming Model was formulated.•Non linear constraints were introduced to model the system main criticalities.•Different cogeneration plant alternatives were analyzed.